'If I learn do we learn?': The link between executive coaching and organizational learning. Issue 4 (September 2013) - Swart, Juani; Harcup, Joy
This article contributes to the organizational learning literature by providing empirical evidence of how coaching enables the translation from individual learning into collective learning, i.e. enacting behaviours, enacting a coaching approach and embedding collective learning processes. It draws on interview data gathered in two law firms wherein learning was the result of executive coaching interventions to pinpoint the mechanisms by which individual and collective learning is interconnected, thereby heeding a call for a more detailed understanding of the mechanisms of learning presented in Management Learning (Bapuji and Crossan, 2004). This enables us to understand the role that coaching plays in the translation from individual to collective learning.